Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, November 13, 1929 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1929)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, November 13, 1929. The second letter to be documented, written from Joseph Roswell Hawley to dear friend Charles Dudley Warner, was written on May 20th, 1847. For context of the time, the President was James K. Polk (the 11th President of the United States), and the nation was embroiled in the Mexican War. There was a slave issue that was considered to be uppermost. Hawley was interested in public affairs, and General Taylor had won his notable victory at Buena Vista. This called for a celebration in the states, specifically New York where Hawley was located at the time. Hawley documented in his letter that he had been chosen as President of the College Union, and he also talks about his current college life.
1 electronic record. Scanned newspaper article. 1 image scans. 1.40 MB (1,473,219 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Letters; Personal correspondence; Newspapers